Restaurant managers’ beliefs about food safety training: An application of the theory of planned behavior - Roberts, Kevin R.; Barrett, Betsy B. (My University, 2012)
Little research has been conducted in applying a theoretical framework to explore restaurant managers’ beliefs about food safety training. Understanding managers’ perceptions of employee food safety training is integral in assuring food safety education is provided for food handlers. The goal of this study was to investigate the antecedents that affect restaurant managers’ willingness to support food safety training for employees utilizing the Theory of Planned Behavior. Results revealed that subjective norms and perceived behavioral control play a key role in determining if a manager or supervisor will offer training to employees. Implications for research and model development are discussed.
embargo 01.2013
Keywords: Food safety training; ServSafe; Theory of planned behavior; Manager; Employee